Shaping the glioblastoma microenvironment to enhance CAR-NK immunotherapy - Tang, Emily; Chen, Jake Y. (Frontiers in Immunology, 2025)
Chimeric antigen receptor–natural killer (CAR-NK) cell therapy has shown favorable results in treating hematological malignancies but with limited efficacy against solid tumors, including glioblastomas, which is partly due to the immunosuppressive microenvironment of solid tumors. This mini review focuses on the various immunosuppressive strategies employed by the glioblastoma microenvironment for immune evasion, including stromal barriers, hypoxic conditions, immunosuppressive cytokines, downregulation of activating ligands, and upregulation of immune checkpoints. A range of emerging strategies has been proposed to counteract these inhibitory effects, such as genetic engineering of NK cells and molecular targeting of the stroma in combination with oncolytic virus therapy. Future single-cell spatiotemporal omics studies are expected to further enable a personalized and dynamic approach to treating glioblastoma with improved outcomes.